Study the Effect of Welding Heat Input on the Microstructure, Hardness, and Impact Toughness of AISI 1015 Steel - Emad Kh. Hamd (Al-Khwarizmi College of Engineering – University of Baghdad, 2018)
In the present study, MIG welding is carried out on low carbon steel type (AISI 1015) by using electrode ER308L of 1.5mm diameter with direct current straight polarity (DCSP). The joint geometry is of a single V-butt joint with one pass welding stroke for different plate thicknesses of 6, 8, and 10 mm. In welding experiments, AISI 1015 plates with dimensions of 200×100mm and edge angle of 60o from both sides are utilized. In this work, three main parameters related to MIG welding process are investigated, which are welding current, welding speed, heat input and plate thickness, and to achieve that three groups of plates are employed each one consists of three plates. The results indicate that increasing the weld heat input (through changing the current and voltage) leads to an increase in widmanstatten ferrite (WF), acicular ferrite (AF) and polygonal ferrite (PF) in FZ region, and a reduction in grain size. It is observed that the micro-hardness of welded AISI 1015 plate increases as the weld heat input decreases. As well as increasing the weld heat input results in an increase in the width of WM and HAZ and a reduction in the impact energy of the weld joint of AISI 1015 at WM region. Also, it is noted the corrosion rate of weld joint increases with increase of Icorr due to increasing in welding current (heat input), corrosion rate increased up to (0.126µm/yr.) with increasing of heat input up to (1.27 KJ/mm).